2013
DOI: 10.1007/s12032-013-0517-8
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of protein phosphatase expression in acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a highly malignant disease of myeloid cell line. AML is the most frequent adult leukemia with inadequate treatment possibility. The protein phosphatases are critical regulators of cell signaling, and deregulation of protein phosphatases always contribute to cell transformation. Although many studies established a relationship between protein phosphatases and leukemia, little is known about the role of this group of proteins in AML. To address this issue, we initially identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…GHR variation has been associated with GH responsiveness in some studies [29, 42-46], but not others [29, 47-51], likely due to methodological differences and/or genetic variations among the populations studied [52]. In common with the latter studies we did not find an association between GHR alleles and 1st-year response to GH treatment in our ISS cohort.…”
Section: Discussionsupporting
confidence: 63%
“…GHR variation has been associated with GH responsiveness in some studies [29, 42-46], but not others [29, 47-51], likely due to methodological differences and/or genetic variations among the populations studied [52]. In common with the latter studies we did not find an association between GHR alleles and 1st-year response to GH treatment in our ISS cohort.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, misregulation of the active phosphatase MTMR3 contributes to susceptibility to gastric and colon carcinomas (14), oral cancer (15), and lung cancer (16), and contributes to metastasis (15,17). Aberrant expression of the inactive MTMR11 has been observed in acute myeloid leukemia (18), acute lymphocytic leukemia (19), and Her2-positive breast cancer (20). Generally, myotubularins are thought to integrate different cellular pathways, through both phosphatidylinositol regulation and protein-protein interactions (2).…”
mentioning
confidence: 99%
“…Indeed, PTPRE (encoded a member of the protein tyrosine phosphatase family) [Kabir et al, 2013], GLRX3 (member of the glutaredoxin oxidoreductase family) [Ohayon et al, 2010], and PPP2R2D (delta Serine-threonine protein phosphatase 2A) [Chen et al, 2012] had been reported in somatic cancer pathologies. MTG1codes for a conserved protein required for mitochondrial translation but remains still poorly understood [Barrientos et al, 2003].…”
Section: Discussionmentioning
confidence: 99%